The Journal of Sexual Medicine (International Society for Sexual Medicine)
Accès par la licence nationale : https://revue-sommaire.data.istex.fr/ark:/67375/8Q1-TM6JSHZX-0 de 2004 à 2012
Keywords: Gynécologie - Obstétrique